Pengaruh steam pretreatment terhadap degradasi selulosa dan limonen pada limbah jeruk dalam produksi biohidrogen - Gita Khaerunnisa; Sarto Sarto; Sutijan Sutijan; Siti Syamsiah (Jurnal Rekayasa Proses, 2018)
This research presents the influence of steam pretreatment to orange waste and its effect on the production of biohydrogen. The steam pretreatments with various times of 2, 4, and 6 hours were applied to the samples. After the pretreatment, the samples were fermented for seven days, and the contents of cellulose, limonene, volatile fatty acid (VFA), and hydrogen were assessed on the days of 1, 2, 3, 5 and 7. Kinetic parameters of hydrogen production were evaluated using the modified Gompertz`s equation. The result of this research showed that the steam pretreatment significantly reduced the cellulose and limonene compounds. The content of cellulose in the substrate after 2, 4 and 6 hours pretreatment were 37.08%; 36.63%; and 15.95%, respectively. Moreover, the content of limonene after pretreatment of 2, 4, and 6 hours were 57.44 ppm; 38.80 ppm; and 36.11 ppm, respectively. Analysis of kinetic parameters of production of hydrogen showed that the maximum productions of hydrogen (Hmax) in the samples after pretreatment of 2, 4, and 6 hours were 11.492 mL; 52.612 mL; 22.345 mL, respectively. The maximum production rates (Rm) at specified pretreatment time (2, 4, and 6 hours) were 9.888 mL H2/hour; 10.008 mL H2/hour; 12.982 mL H2/hour and the lag phases were 49.689 hours; 24.742 hours; and 24.885 hours. The study elucidated that applying pretreatment for 4 hours gives the optimum condition for hydrogen production.